Novel Insights Into Pathogenesis and Therapeutic Strategies of Hepatic Encephalopathy, From the Gut Microbiota Perspective - Liu, Jiachen; Xu, Yantao; Jiang, Bimei (Frontiers in Cellular and Infection Microbiology, 2021)
Since the 1950s, gradual changes in the gut microbiota of patients with hepatic encephalopathy have been observed. Previous research has indicated potential associations between the gut and brain, and the gut microbiota is becoming a hot topic in research on diseases of the nervous system. However, for the past few decades, studies of hepatic encephalopathy have been restricted to controlling the gut microbiota during macroscopic manipulation, such as probiotic intervention, while its clinical use remains controversial, and the cellular mechanisms underlying this condition are still poorly understood. This thesis seeks to comprehensively understand and explain the role of gut microbiota in hepatic encephalopathy as well as analyse the effects of intervention by regulating the gut microbiota. Evidence is presented that shows that dysbiosis of gut microbiota is the primary pathological driver of hepatic encephalopathy and impacts pathologic progression via complex regulatory networks. As a result, suggestions were identified for future mechanistic research and improvements in therapeutic strategies for hepatic encephalopathy.